1967
DOI: 10.1002/j.2333-8504.1967.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Percentage of Pupillary Dilation With Other Measures of Difficulty of Mental Multiplication Items1

Abstract: The purpose of this study was to compare four measures of difficulty of mental multiplication items: percentage of pupillary dilation, latency of solution, number of correct responses, and judgment of item difficulty. Sixteen multiplication problems, classified into four levels of difficulty, were presented visually to 13 Ss. The Ss verbalized their solutions to the problems. Analyses of variance and correlation coefficients were computed. It was concluded that all four measures of difficulty were useful but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Payne, Parry and Harasymiw (1967) plotted the average pupil diameter of one S over all items at each successive~sec interval following item presentation. The average response curve accelerated rapidly during the 4 sec following item presentation and then leveledoff and remained at a fairly constant value until a solution was reported.…”
Section: Pupillary Dilation and Infonnation Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Payne, Parry and Harasymiw (1967) plotted the average pupil diameter of one S over all items at each successive~sec interval following item presentation. The average response curve accelerated rapidly during the 4 sec following item presentation and then leveledoff and remained at a fairly constant value until a solution was reported.…”
Section: Pupillary Dilation and Infonnation Processingmentioning
confidence: 99%
“…In the present study, all data points within the control and problem solving intervals were averaged rather than averaging only points within the 2.5 sec intervals preceding and following presentation of the stimulus. Problems associated with both of these procedures are discussed, and the suitability of a percentage measure of dilation is questioned, in Payne, Parry and Harasymiw (1967). They conclude that simple difference measures may be preferable to percentage measures.…”
Section: Measurement Of Percentage Of Pupillary Dilationmentioning
confidence: 99%
“…Previous analyses of internal tobacco industry documents have described the global strategy of transnational tobacco companies (TTCs) to undermine scientific evidence demonstrating the harmful health effects of SHS through covertly recruiting scientists in China [ 16 20 ] and globally [ 21 25 ], influencing media coverage of SHS issues, and creating front organizations [ 21 , 23 , 26 – 29 ]. Previous research has also shown that TTCs have alternatively promoted ineffective ventilation and separate seating for smokers and nonsmokers in hospitality venues with the aim of undermining smoke-free legislation [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%